Method for preparing solid-state electrode section sample and application

By fixing the solid-state electrode within a flexible package and using argon-ion polishing technology, the problems of mechanical deformation and environmental sensitivity in the preparation of solid-state battery electrode cross-section samples were solved, achieving efficient and clear cross-section sample preparation.

CN121026727APending Publication Date: 2025-11-28CHINA AUTOMOTIVE BATTERY RES INST CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202511202514.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-26
Publication Date
2025-11-28

AI Technical Summary

Technical Problem

Existing technologies often encounter problems such as slagging, cracking, and tensile deformation when preparing solid-state battery electrode cross-section samples due to insufficient cohesion. Furthermore, the electrolyte material is sensitive to the environment when using resin casting, which affects the success rate and applicability of sample preparation.

Method used

A solid electrode is fixed in a flexible package, and argon ion polishing technology is used to remove the flexible material and the area to be removed to prepare a solid electrode cross-section sample, reducing the influence of mechanical deformation and ion flow.

Benefits of technology

It improves the sample preparation success rate, maintains the original morphology of the microporous structure, reduces adverse phenomena such as melting, twisting, and powder shedding, and obtains clear cross-sectional samples.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121026727A_ABST
    Figure CN121026727A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a solid-state electrode section sample and application, and the method comprises the following steps: fixing a solid-state electrode in a flexible packaging body to obtain a pretreated sample; the pretreated sample is installed in an argon ion polishing machine, and the axis direction of an argon ion beam is aligned with one edge area of the pretreated sample; and performing argon ion polishing treatment on the pretreated sample, so that the argon ion beam can remove a part of the flexible material on one side, facing the source direction of the argon ion beam, of the flexible packaging body and a to-be-removed area of the solid-state electrode, thereby obtaining the section sample of the solid-state electrode. Therefore, the original morphology of the microcosmic porous structure of the solid-state electrode can be kept, and the possibility of sample preparation and shooting failure caused by the conditions of melting, distortion, powder falling, cracking and the like due to the fact that the electrode structure is influenced by argon ion flow and the like is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the field of material testing, in particular, to a method for preparing a solid-state electrode cross-section sample and applications. BACKGROUND

[0002] As a new battery technology that is expected to achieve high energy density and high safety at the same time, solid-state batteries have gradually become a research hotspot worldwide. The microstructure of solid-state battery electrodes directly affects the quality of electrical performance and is directly related to the cycle performance, service life and safety of the battery.

[0003] Microscopic morphology observation of solid-state battery electrode materials can obtain key information such as particle size, thickness, structure, compaction, and coating distribution of the electrode material, and is an important means of material performance testing. The most commonly used means for material microscopic morphology observation is scanning electron microscopy (SEM), which has the ability to directly image the microstructure of the sample surface at magnifications of several hundred to hundreds of thousands.

[0004] In related technologies, when preparing a solid-state battery electrode cross-section sample containing a solid-state electrolyte particle component, the electrolyte material is often pressed into a sheet or block, or the electrolyte material is mixed with battery active materials and then pressed into a sheet or block. Compared with traditional lithium-ion battery electrodes with a foil-coating structure, the cohesion of solid-state battery electrode samples is limited, and phenomena such as slagging, cracking, and tensile deformation often occur during sample preparation and cross-section polishing, affecting the success rate of sample preparation. Or use resin to cast and fix the material particles, but since the sulfides and halides commonly used in solid-state batteries are sensitive to the environment and may react with the resin components, the applicability of this method is affected.

[0005] Therefore, the method for preparing a solid-state electrode cross-section sample still needs to be further improved.

[0006] It should be noted that the above statements are only used to provide background technical information related to the present application, and do not necessarily constitute prior art. SUMMARY

[0007] In a first aspect of the present application, a method for preparing a solid-state electrode cross-section sample is provided, comprising:

[0008] Fixing the solid-state electrode in a flexible packaging body to obtain a pretreated sample;

[0009] Installing the pretreated sample in an argon ion polishing machine, and aligning the axis direction of the argon ion beam with an edge region of the pretreated sample;

[0010] The argon ion polishing treatment is performed on the pretreated sample, so that the argon ion beam can remove part of the flexible material on the side of the flexible package facing the direction of the source of the argon ion beam and the region to be removed of the solid-state electrode, to obtain the solid-state electrode cross-section sample.

[0011] The application prepares the solid-state electrode cross-section sample by the above method. Fixing the solid-state electrode in the flexible package not only reduces the potential influence of liquid medicine on the surface of the solid-state electrode, but also reduces the possibility of failure in sample preparation and shooting due to melting, distortion, powdering, cracking and other situations of the electrode structure caused by ion flow during argon ion polishing and topography characterization. At the same time, the argon ion polishing method is used to prepare the solid-state electrode cross-section sample, which maximally reduces mechanical deformation and maintains the original morphology of the micro-porous structure. The argon ion beam first penetrates the flexible package and then penetrates the solid-state electrode to be tested in the polishing process, which reduces the possibility of edge ablation, melting and other adverse conditions.

[0012] In addition, the preparation method according to the above embodiments of the application can also have the following additional technical features:

[0013] In some embodiments of the application, the flexible material of the flexible package includes at least one of an aluminum foil, a copper foil and an aluminum plastic composite film. In this way, the powdering, cracking and other situations of the solid-state electrode caused by the influence of ion flow can be reduced.

[0014] In some embodiments of the application, the thickness of the flexible material of the flexible package is 10-30 μm. In this way, the influence range of abnormal phenomena such as ablation and melting is within the thickness range of the flexible package, reducing the influence on the solid-state electrode.

[0015] In some embodiments of the application, the shape of the flexible package includes at least one of a bag shape, a U shape and a flat box shape. In this way, the powdering, cracking and other situations of the solid-state electrode caused by the influence of ion flow can be reduced.

[0016] In some embodiments of the application, the flexible package at least wraps three surfaces of the solid-state electrode. In this way, the flexible package can better wrap the solid-state electrode, thereby reducing the powdering, cracking and other situations of the solid-state electrode caused by the influence of ion flow.

[0017] In some embodiments of the application, the method of fixing the solid-state electrode in the flexible package includes at least one of gluing, air extraction, cold pressing and hot pressing. In this way, there are more optional fixing methods.

[0018] In some embodiments of the application, the gap between the solid-state electrode and the flexible package is less than or equal to 5 μm. In this way, the occurrence of burr phenomenon during argon ion polishing can be reduced.

[0019] In some embodiments of the present application, the pre-processed sample extends 50-150 μm beyond the baffle of the argon ion polisher. In this way, the range of the argon ion beam can be controlled, non-targeted areas can be protected, and the polishing effect can be optimized.

[0020] In some embodiments of the present application, the pressure in the chamber of the argon ion polisher during the argon ion polishing process is less than or equal to 2 x 10 -3 Pa, the working voltage of the argon ion source is 3-8 kV, and the polishing time is 0.5-3 h. In this way, the polishing effect can be improved, and a relatively smooth solid electrode cross-section can be obtained.

[0021] In a second aspect of the present application, the solid electrode cross-section sample prepared by the method of the first aspect of the present application is applied to scanning electron microscopy characterization. It should be noted that the features and effects described for the method of the first aspect of the present application are also applicable to the application of the second aspect of the present application, which will not be described here. BRIEF DESCRIPTION OF DRAWINGS

[0022] The above and / or additional aspects and advantages of the present application will become apparent and be readily understood from the following description, taken in conjunction with the following drawings, in which:

[0023] Figure 1 Preparation flow chart of the solid electrode cross-section sample of one embodiment of the present application.

[0024] Figure 2 SEM photo of the solid electrode cross-section sample of one embodiment of the present application. DETAILED DESCRIPTION

[0025] Embodiments of the present application are described in detail below, examples of which are shown in the accompanying drawings, but there will be cases where unnecessary detailed description is omitted. For example, there are cases where detailed description of matters well known to those skilled in the art, repeated description of substantially the same structure, is omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate understanding by those skilled in the art. In addition, the drawings and the following description are provided to enable those skilled in the art to fully understand the present application, and are not intended to limit the subject matter recited in the claims.

[0026] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs; the terminology used in the present application is for the purpose of describing particular embodiments only and is not intended to be limiting of the present application; unless otherwise specified, the numerical values of the parameters mentioned in the present application can be measured by various measurement methods commonly used in the art (for example, tests can be performed according to the methods given in the embodiments of the present application).

[0027] The terms "comprise" and "have" and any variations thereof in the specification and claims of this application are open-ended transitional phrases, i.e., including, but not limited to, whatever follows the term(s) in the list of elements.

[0028] In the description of the application, whether using the word "about" or "approximately", all numbers disclosed herein are approximate. Each numerical value is intended to encompass numbers that are close to and fall within one-tenth of the indicated value, unless indicated otherwise. Numbers that are relatively close to the stated value within 10% of the stated value are typically considered the same as the stated value for the purpose of this application.

[0029] The ranges disclosed herein are defined by the lower and upper limits of the range, given by selecting a lower limit and an upper limit, the selected lower limit and upper limit defining the boundaries of the particular range. The ranges defined by this approach can be inclusive or exclusive of the end values, and can be arbitrarily combined, i.e., any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a particular parameter, it is understood that ranges of 60-110 and 80-120 are also contemplated. In addition, if minimum range values of 1 and 2 are listed, and if maximum range values of 3, 4, and 5 are listed, then the following ranges are all contemplated: 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5. In this application, unless otherwise stated, a numerical range "a-b" indicates a shorthand way of describing all the individual real combinations of a to b, where a and b are real numbers. For example, the numerical range "0-5" indicates that all the real numbers between "0-5" have been listed herein, "0-5" is just a shorthand way of describing these numerical combinations. In addition, when a parameter is stated to be an integer ≥ 2, it is equivalent to disclose that the parameter is, for example, integer 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0030] In the description of the application, it is to be understood that the terms "length", "width", "thickness", "upper", "lower", "front", "back", "left", "right", etc., indicate the orientation or positional relationship based on the orientation or positional relationship shown in the drawings, and are only for the convenience of describing the application and simplifying the description, and do not indicate or imply that the device or element referred to must have a particular orientation, be constructed and operated in a particular orientation, and therefore cannot be understood as a limitation on the application.

[0031] In the present application, the order of writing each step does not mean a strict execution order and does not constitute any limitation on the implementation process. The specific execution order of each step should be determined by its function and possible internal logic. If not specifically stated, all steps of the present application can be performed sequentially or randomly, and the preferred order is sequential. For example, the method comprises steps (a) and (b), which means that the method can comprise sequentially performed steps (a) and (b), or sequentially performed steps (b) and (a). For example, the method also comprises step (c), which means that step (c) can be added to the method in any order, for example, the method can comprise steps (a), (b) and (c), or steps (a), (c) and (b), or steps (c), (a) and (b), etc.

[0032] If not specifically stated, all embodiments and optional embodiments of the present application can be combined with each other to form new technical solutions.

[0033] If not specifically stated, all technical features and optional technical features of the present application can be combined with each other to form new technical solutions.

[0034] In the first aspect of the present application, the present application provides a method for preparing a solid-state electrode cross-section sample, referring to Figure 1 The method comprises:

[0035] S1: fixing the solid-state electrode in the flexible packaging body to obtain a pretreated sample.

[0036] In some embodiments of the present application, the flexible material of the flexible packaging body comprises at least one of an aluminum foil, a copper foil, and an aluminum plastic composite film. The material constituting the flexible packaging body can also be a metal or non-metal material that is flat and wrinkle-free, has a certain flexibility and toughness. Using the above-mentioned materials to constitute the packaging body can reduce the situation that the solid-state electrode is affected by ion flow and falls off, cracks, etc.

[0037] In some embodiments of the present application, the shape of the flexible packaging body comprises at least one of a bag shape, a U shape, and a flat box shape. In this way, the situation that the solid-state electrode is affected by ion flow and falls off, cracks, etc. can be reduced.

[0038] In some embodiments of the present application, the flexible packaging body at least wraps three surfaces of the solid-state electrode. It can be understood that the flexible packaging body should at least wrap three directions of the solid-state electrode in the up, down, left, right, front and back directions (only for conceptual description, and should not be regarded as a limitation on the present embodiment). In this way, the flexible packaging body can better wrap the solid-state electrode, thereby reducing the situation that the solid-state electrode is affected by ion flow and falls off, cracks, etc.

[0039] In some embodiments of the present application, the method of fixing the solid-state electrode in the flexible packaging body includes at least one of gluing, vacuumizing, cold pressing, and hot pressing. When the fixing method is gluing, the solid-state electrode and the flexible packaging body should be flatly attached after gluing, without wrinkles or bulges, and the surface of the solid-state electrode within 1-2 mm around the center of the polished area should not be glued.

[0040] In some embodiments of the present application, the gap between the solid-state electrode and the flexible packaging body is less than or equal to 5 μm, for example, it can be 1 μm, 2 μm, 3 μm, 4 μm, or 5 μm, etc. It can be understood that the solid-state electrode is closely attached to the flexible packaging body. Thus, the occurrence of the burr phenomenon during argon ion polishing can be reduced.

[0041] In some embodiments of the present application, before fixing the solid-state electrode in the flexible packaging body, the solid-state electrode containing the solid-state electrolyte can be formed into a square sample, and the position, orientation, etc. of the sample on the original electrode are recorded as necessary. The solid-state electrode used can be an electrolyte layer for a sulfide all-solid-state battery, with a thickness of 30-200 μm (such as 30 μm, 50 μm, 80 μm, 100 μm, 130 μm, 150 μm, 180 μm, or 200 μm, etc.), and after sampling and cutting, it is in the form of a cuboid sheet, with a size of 8 mm x 10 mm. It can be understood that during the cutting process, the cutting mechanism only processes the edges of the solid-state electrode, and the overall structure inside the solid-state electrode can remain intact. Moreover, the appearance of the solid-state electrode after cutting can remain complete and compact, without phenomena such as fragmentation and delamination.

[0042] In some embodiments of the present application, the composition containing multiple electrode assemblies can be processed at one time under the condition that the equipment processing depth and speed are supported, for example, the electrolyte layer containing the sulfide solid-state electrolyte is combined with the negative electrode layer containing the sulfide solid-state electrolyte and the silicon-carbon powder to form a composition with the flexible packaging body, and the cross-section polishing operation is performed on the argon ion polishing machine. It can be understood that the structure of the solid-state electrode is not limited to a single piece or a single type, and can be extended to a sample containing multiple electrolyte layers and active material layers.

[0043] In some embodiments of the present application, the solid-state electrode is placed in the flexible packaging body, and the position of the solid-state electrode and the flexible packaging body is fixed relative to each other. The preprocessed sample formed by the solid-state electrode and the flexible packaging body is shaped as necessary, so as to have a flat side edge.

[0044] S2: The preprocessed sample is installed in the argon ion polishing machine, and the axis direction of the argon ion beam is aligned with one edge region of the preprocessed sample.

[0045] It can be understood that the preprocessed sample is in the form of a cuboid sheet, and the edge region is one side of the sheet structure.

[0046] In some embodiments of the present application, when the pre-processed sample is installed on the argon ion polishing machine station, the clamp of the argon ion polishing machine is properly pressed to make the solid electrode and the flexible packaging body adhere to each other during the argon ion polishing process.

[0047] S3: argon ion polishing treatment is performed on the pre-processed sample, so that the argon ion beam can remove the flexible material on the side of the flexible packaging body facing the source direction of the argon ion beam and the region to be removed of the solid electrode, to obtain a solid electrode cross-section sample.

[0048] In some embodiments of the present application, the thickness of the flexible material of the flexible packaging body is 10-30 μm, for example, it can be 10 μm, 15 μm, 20 μm, 25 μm or 30 μm, etc. After the solid electrode is wrapped with the flexible packaging body, in the argon ion polishing process, the argon ion beam first penetrates the flexible packaging body on the side facing the argon ion source, and then penetrates the solid electrode. When melting and other phenomena occur in the argon ion polishing process due to high energy, it most commonly occurs in the 1-10 μm thick region first affected by the ion flow, so this packaging structure can make the ablation, melting and other abnormal phenomena only affect the thickness of the flexible packaging body, and less affect the solid electrode, thereby reducing the influence of abnormal phenomena on the morphology characterization. The thickness of the flexible material of the flexible packaging body in the above range can make the ablation, melting and other abnormal phenomena only affect the thickness of the flexible packaging body, reducing the influence on the solid electrode.

[0049] When preparing a cross-section sample by argon ion polishing, a baffle is usually arranged between the argon ion source and the sample to be polished to control the boundary between the region to be removed and the region not to be removed on the sample to be polished. In some embodiments of the present application, the region protruding from the baffle can be partially or completely removed by the ion beam in the polishing process, while the region not protruding from the baffle will not be removed by the ion beam. In the description of the present application, the "baffle" is a description of a component in the ion polishing device that has a specific function, and its actual shape includes but is not limited to a thin plate shape, and should not be considered as a limitation on the scope of the claims of the present application.

[0050] It can be understood that in the polishing process, in order to ensure that the argon ion beam can penetrate and cut the edge region of the pre-processed sample, the working parameters of the argon ion polishing machine need to be adjusted according to the actual needs, so that the emission direction of the argon ion beam can penetrate the part of the pre-processed sample protruding from the baffle, thereby forming a polished surface in the thickness direction of the solid electrode with a width sufficient for morphology characterization.

[0051] It can be understood that when part of the pre-processed sample is covered by the baffle, the pre-processed sample in the region outside the covered region and irradiated by the argon ion beam will have its flexible material on the side facing the argon ion beam removed after polishing.

[0052] In some embodiments of the present application, the distance between the pre-processed sample and the baffle of the argon ion polishing machine is 50-150 μm, for example, it can be 50 μm, 80 μm, 100 μm, 130 μm or 150 μm, etc. In this way, the range of the argon ion beam can be controlled, the non-target area can be protected, and the polishing effect can be optimized.

[0053] In some embodiments of the present application, after the pre-processed sample is fixed in the argon ion polishing machine, the pre-processed sample is placed in a negative pressure sealed environment to reduce the influence of impurities in the external environment on the cutting of the argon ion beam.

[0054] In some embodiments of the present application, the pressure in the cabin of the argon ion polishing machine during the argon ion polishing process is less than or equal to 2 x 10 -3 Pa, for example, it can be 2 x 10 -3 Pa, 2 x 10 -4 Pa, 2 x 10 -5 Pa, 2 x 10 -6 Pa, 2 x 10 -7 Pa or 1 x 10 -3 Pa, etc.; the working voltage of the argon ion source is 3-8 kV, for example, it can be 3 kV, 4 kV, 5 kV, 6 kV, 7 kV or 8 kV, etc.; the polishing time is 0.5-3 h, for example, it can be 0.5 h, 1 h, 1.5 h, 2 h, 2.5 h or 3 h, etc. As an example, a working voltage of 4 kV can be used for polishing for 2 h. According to actual needs, a person skilled in the art can also sequentially perform a combination process of multiple polishing voltages and polishing times to take into account time, polishing details, effect and equipment life, for example, first use 5 kV for 1 h, and then use 4 kV for 0.5 h. In this way, the polishing effect can be improved, and a relatively smooth solid-state electrode cross section can be obtained.

[0055] In some embodiments of the present application, the cross section formed by the argon ion polishing is flat, wherein the middle section part penetrates the entire thickness of the planned observation area of the solid-state electrode sample to be measured, the depth is uniform and suitable for the area for topographic characterization, and the width should be not less than 0.3 mm.

[0056] In some embodiments of the present application, the argon ion polishing process can be performed at room temperature, or liquid nitrogen can be used to overall cool the sample cabin of the argon ion polishing machine, and the pre-processed sample is polished at an initial temperature of -50°C. By this processing method, the phenomenon that the particle interface on the solid-state electrode cross section is melted due to excessive local energy and is not clear and not suitable for observation can be less likely to occur.

[0057] The application fixes the solid-state electrode in the flexible packaging body by the above method, which not only reduces the potential influence of liquid medicine on the surface of the solid-state electrode, but also reduces the possibility of sample preparation and shooting failure caused by melting, distortion, powdering, cracking and other situations due to the influence of ion flow on the electrode structure during argon ion polishing and morphology characterization; at the same time, the solid-state electrode cross-section sample is prepared by using the argon ion polishing method, which maximally reduces mechanical deformation and maintains the original morphology of the micro-porous structure, so that the argon ion beam first penetrates the flexible packaging body and then penetrates the solid-state electrode to be tested, thereby reducing the possibility of edge ablation, melting and other situations that are not conducive to observation.

[0058] In the second aspect of the application, the application proposes that the solid-state electrode cross-section sample prepared by the method of the first aspect of the application is applied to scanning electron microscope characterization. It should be noted that the features and effects described for the method of the first aspect of the application are also applicable to the application of the second aspect of the application, which will not be described here.

[0059] Specifically, the above solid-state electrode cross-section sample can be installed on a sample stage, and then scanning electron microscope shooting is performed. The fixing method of the solid-state electrode cross-section sample on the sample stage can be a clamp, a fixture or conductive adhesive; when fixed, the side with stronger conductivity in the solid-state electrode cross-section sample should be fixed on the sample stage first; if the electrolyte component in the solid-state electrode is sensitive to the environment and cannot be exposed to the usual indoor environment, a special sealed transfer container should be used when the pretreated sample is transferred from the outside of the argon ion polishing machine to the inside of the argon ion polishing machine for polishing process, and when the polishing process is completed and the sample is transferred from the argon ion polishing machine to the scanning electron microscope for shooting, in order to ensure that the sample does not fail.

[0060] In some other embodiments of the application, in order to improve the imaging quality during scanning electron microscope shooting, the observation section of the solid-state electrode cross-section sample can be treated by gold spraying or the like before shooting.

[0061] The above description of each embodiment tends to emphasize the differences between each embodiment, and the same or similar parts can be referred to each other, and will not be described here for the sake of brevity.

[0062] The scheme of the application will be described below through specific embodiments. It should be noted that the following embodiments are only used to illustrate the application, and should not be regarded as limiting the scope of the application. If the specific technology or condition is not specified in the embodiments, the technology or condition described in the literature in the art or according to the product manual is used. If the reagent or instrument is not specified by the manufacturer, it is a conventional product that can be obtained by purchase.

[0063] Example 1

[0064] (1) Shape the solid electrode containing sulfide solid electrolyte into a square sample, and make necessary records of the position and orientation of the sample on the original electrode. The thickness of the solid electrode is 130-135μm, and the size of the sample after cutting for argon ion polishing is 8mm×10mm.

[0065] (2) The solid electrode is placed in a package made of bag-shaped aluminum foil (20 μm thick), and the solid electrode and the flexible package are fixed in relative position by adhesive. The pre-treated sample composed of the solid electrode and the flexible package is shaped as necessary to make it have a straight edge on one side.

[0066] (3) The pre-treated sample consisting of a solid electrode and a flexible packaging body is installed on the station of the argon ion polishing machine, so that the direction of the ion beam emission is perpendicular to the plane where the solid electrode sample is located, and the axis direction of the most concentrated argon ion flow is aligned with the part of the pre-treated sample that extends out of the polishing machine baffle. At the position where the argon ion flow axis is aligned, the gap between the solid electrode and the flexible packaging body is 3μm, and the length of the pre-treated sample extending out of the argon ion polishing machine baffle is 100μm.

[0067] (4) Adjust the operating parameters of the argon ion polishing machine to ensure that it can penetrate the combined thickness of the layer facing the ion beam direction of the packaging and the solid electrode sample, forming a polished surface with a width sufficient for scanning electron microscopy; the chamber pressure of the argon ion polishing machine is 2×10 when the polishing process is started. -3 Pa, the working voltage of the ion source is 5kV, and the polishing time is 2h;

[0068] (5) Perform ion polishing to obtain a solid electrode cross-section sample. Mount the solid electrode cross-section sample on the sample stage and then perform scanning electron microscopy (SEM) imaging.

[0069] Characterization results as follows Figure 2 As shown, the cross-section of the solid electrode is clearly visible.

[0070] It should be noted that this application is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments with the same structure and effect as the technical concept within the scope of this application are included in the technical scope of this application. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, without departing from the spirit of this application, are also included in the scope of this application.

Claims

1. A method for preparing a solid electrode cross-section sample, characterized in that, include: Solid electrodes are fixed within flexible packaging to obtain pretreated samples; The pretreated sample is mounted in an argon ion polishing machine, with the axial direction of the argon ion beam aligned with an edge region of the pretreated sample. The pretreated sample is subjected to argon ion polishing, which enables the argon ion beam to remove a portion of the flexible material on the side of the flexible package facing the direction of the argon ion beam source, as well as the area of ​​the solid electrode to be removed, to obtain a cross-sectional sample of the solid electrode.

2. The method according to claim 1, characterized in that, The flexible material of the flexible packaging body includes at least one of aluminum foil, copper foil, and aluminum-plastic composite film.

3. The method according to claim 2, characterized in that, The thickness of the flexible material in the flexible packaging body is 10μm-30μm.

4. The method according to claim 1 or 2, characterized in that, The shape of the flexible packaging includes at least one of bag-shaped, U-shaped, and flat box-shaped.

5. The method according to claim 1, characterized in that, The flexible packaging body covers at least three surfaces of the solid electrode.

6. The method according to claim 1, characterized in that, The method for fixing the solid electrode within the flexible packaging body includes at least one of adhesive bonding, vacuuming, cold pressing, and hot pressing.

7. The method according to claim 6, characterized in that, The gap between the solid electrode and the flexible packaging body is less than or equal to 5 μm.

8. The method according to claim 1, characterized in that, The distance by which the pretreated sample extends beyond the baffle of the argon ion polishing machine is 50μm-150μm.

9. The method according to claim 1, characterized in that, During the argon ion polishing process, the internal air pressure of the argon ion polishing machine is less than or equal to 2 × 10⁻⁶. -3 Pa, the working voltage of the argon ion source is 3kV-8kV, and the polishing time is 0.5h-3h.

10. A solid electrode cross-section sample prepared by the method according to any one of claims 1-9 is used for scanning electron microscopy characterization.

Citation Information

Patent Citations

  • Preparation method of thin-film material section scanning electron microscope sample

    CN111721792A

  • Treatment method for cutting section of battery diaphragm by argon ion beams

    CN112285139A

  • Preparation method of solid-state battery scanning electron microscope sample

    CN118857882A

  • Preparation method of scanning electron microscope sample

    CN120009024A

  • Inspecting and analyzing method and sample manufacturing apparatus

    JP2001345360A